2010
DOI: 10.1088/0953-8984/22/44/445303
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties through graphene-based fractal and periodic magnetic barriers

Abstract: We investigate the transmission of electrons in a single layer graphene system subjected to nanoscale magnetic barriers and wells arranged in the Cantor pre-fractal and the finite periodic distribution. We find that the angular threshold and angular asymmetry of the transmission spectra are closely related to the ratio between the magnitude of the vector potential and the incident energy (|A|/E), which also determine the number and width of the resonant domains for the finite periodically magnetic modulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…13,14 However, experimentally, most observations so far have been attributed to the extrinsic SHE. 9À11 Some recent observation of the nonlocal SHE was also found in various systems, 5,11,15 including graphene 6,16,17 which can only be explained by the intrinsic mechanism. 18 Considerable e®ort in this direction has already revealed the unique features of spin-polarized electron transport in the so-called two-terminal nano-or mesoscopic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 However, experimentally, most observations so far have been attributed to the extrinsic SHE. 9À11 Some recent observation of the nonlocal SHE was also found in various systems, 5,11,15 including graphene 6,16,17 which can only be explained by the intrinsic mechanism. 18 Considerable e®ort in this direction has already revealed the unique features of spin-polarized electron transport in the so-called two-terminal nano-or mesoscopic devices.…”
Section: Introductionmentioning
confidence: 99%
“…1 Spin separation in semiconductors is not only possible, but also quite natural, so that manipulating spin properties of charge carriers in electronics is a promising¯eld of research. 2À4 Recently, di®erent types of SHE were reported for di®erent geometrical setups of both magnetic 5,6 and nonmagnetic materials. 7,8 Local SHE often attributed both as extrinsic SHE, 9À11 and intrinsic SHE.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, self-similarity in aperiodic structures in graphene is not the exception. Several works claim that the transmission probability sustains self-similar characteristics in Fibonacci and Thue-Morse superlattices 1518 , but once again the scale factors that connect the transmission patterns are not derived. Recently, we have shown that the transmission properties of graphene subjected to self-similar and self-affine multi-barrier structures present self-similar characteristics 1921 .…”
Section: Introductionmentioning
confidence: 99%
“…So, by considering the importance of the quasi-periodic modulation, from both the fundamental and technological standpoints, it seems natural that it be an extension for any novel material. To this respect graphene is not the exception, and in the last years the interest in aperiodic or quasi-periodic modulation in graphene is rising [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. All these studies focus primarily on monolayer graphene, and the preferred mechanism to create the quasi-periodic pattern has been the electrostatic field effect.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies focus primarily on monolayer graphene, and the preferred mechanism to create the quasi-periodic pattern has been the electrostatic field effect. So far, the quasi-periodic patterns studied in graphene have been Cantor [33][34][35], Fibonacci [36][37][38][39][40], Thue-Morse [41][42][43][44][45][46][47], Double-Period [48] and Gaussian [49,50]. One of the most remarkable characteristics of quasi-periodic patterns in graphene, regardless of the quasi-periodic sequence used, is a zero-gap associated to an unusual Dirac point.…”
Section: Introductionmentioning
confidence: 99%